MEMBANGUN SINERGI PENDIDIKAN ANAK USIA DINI: TINJAUAN ATAS PERSEPSI ORANG TUA DI DESA AMAWANG KIRI KECAMATAN KANDANGAN - Farina, Mahlida; Ahmad Suriansyah; Rizky Amelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Parental involvement in early childhood education serves as a crucial foundation for shaping children's character, moral values, and basic skills. Although formal education is available, the role of the family remains a primary factor in a child’s development. However, the degree of parental involvement varies depending on social, economic, and educational backgrounds. This study aims to describe the forms of parental involvement in early childhood education and the influencing factors. A qualitative approach with a case study method was employed. Data were collected through interviews and observations involving selected informants. The findings reveal three main points. First, parents generally hold a positive perception of the importance of early childhood education. Second, the forms of involvement vary, ranging from actively assisting children’s learning to fully delegating the responsibility to a partner or educational institution. Third, involvement is influenced by factors such as time availability, spousal support, availability of learning resources at home, and the educational background of parents. These findings highlight the significance of family support as the primary learning environment from an early age.